I will survive! - Lamangan, Joel.; Regal Entertainment (Quezon City Regal Entertainment, 2004)
A story about four friends who try to survive motherhood in a crazy world. Career woman Cynthia has a son with raging hormones and a husband who has stopped making love to her after 20 years of marriage. Mylene is an overseas contract worker based in Qatar. While she desperately tries to reach out to her emotionally distant younger daughter, Mylene suspects that her husband, also an OFW, has a mistress in the country where he works. Louise is a former beauty queen who has a doting husband who shower her with too much affection, and a pre-teen daughter who resents her for being beautiful. Mandy a gym instructor, hides his homosexuality from his adopted sons. Dindo, Mandy's 13-year old son, suspects, that dad is gay, and his leading questions give Mandy reason to believe that Dindo might also be gay.
VCD
Maricel Soriano, Dina Bonnevie, Eric Quizon, and Judy Ann Santos
Keywords: Motherhood; Comedy films; Feature films